RETRACTED: Business Ethics and Irrationality in SME During COVID-19: Does It Impact on Sustainable Business Resilience? - Huang, Xiang; Chau, Ka Yin; Tang, Yuk Ming; Iqbal, Wasim (Frontiers in Environmental Science, 2022)
The economic impact of COVID-19 has raised the number of unemployment and necessitates on the establishment of new businesses to sustain the economy. Therefore, the objective of this study is to incorporate loss aversion, cardinal effect, and behavior groups as the variables to assess the link between illogical conduct and business ethics in SMEs. It also explores on the position of altruism as a mediating factor in economic conduct. A survey involving 300 small and medium-sized businesses (SMEs) was undertaken in China. Results from the structural equation model (SEM) indicate that basic phenomena and group behavior are strongly linked to business ethics. Meanwhile, all coefficient estimates for the interaction term have recorded positive values, regardless whether the control variables are included. Surprisingly, the consumer products subgroup (0.86%) exhibits a higher average rise in volatility when UPE sensitivity is greater than non-consumer equities (0.55%). This study has effectively minimized irrational media behavior in China by combining altruism with business ethics. Furthermore, it was found that marketing strategies discriminate between altruism’s moral and financial effects.